Comparative analysis of intense multidirectional movements in youth handball and soccer player - Kovács, M.; Pocsai, B.; Zsanda, E.; Pöszmet, T.; Balogh, L.; Pucsok, J. M. (STADIUM - Hungarian Journal of Sport Sciences, 2020)
Modern soccer is characterized by short distance multidirectional movements. Elite level players execute a large number of micromovements of all kinds. Like in handball game situations in soccer usually occur in small areas. We investigated, whether soccer players may be able to perform accelerations, decelerations, intense starting movements and turns at the same level as handball players. We utilized the Speed Court movement analysis system to prove our hypotheses. We measured youth athletes, they executed two testing protocols. High-quality speed, agility, spatial awareness, and decision-making capabilities were required by the participants. We designed two protocols called the "60-meter chase", and the "30-second chase" to mimic the situations tend to occur in a game. Each participant was asked to perform the test protocols three-times, we registered the best try, after 12 weeks of practice, the athletes repeatedly executed the two protocols. We also performed a body composition analysis, which demonstrated similar data for the two groups. We concluded that soccer players were able to perform at the same level as handball players, some of them even outperformed their counterparts.